Ocular Toxicity of Mirvetuximab. Issue 2 (February 2019) - Corbelli, Eleonora; Miserocchi, Elisabetta; Marchese, Alessandro; Giuffrè, Chiara; Berchicci, Luigi; Sacconi, Riccardo; Bandello, Francesco; Modorati, Giulio Maria
Abstract : Purpose: To report the clinical features and outcomes of corneal toxicity following mirvetuximab soravtansine therapy. Methods: Five patients who were treated with mirvetuximab soravtansine were evaluated in our hospital for ocular symptoms during a period of 5 months between December 2017 and April 2018. A complete ophthalmologic examination, including anterior segment infrared reflectance (AS-IR) and anterior segment optical coherence tomography (AS-OCT), was performed. Results: All 5 patients were female (average age, 62.4 ± 5.5 years) and being treated for advanced epithelial ovarian cancer, primary peritoneal cancer, or fallopian tube cancer. Both eyes were involved in each case. Patients complained of blurred vision (n = 5), ocular pain (n = 2), tearing (n = 5), foreign-body sensation (n = 4), and photophobia (n = 4). Slit-lamp examination demonstrated fine corneal subepithelial opacities, mainly involving the corneal periphery migrating toward the center. AS-IR revealed the presence of hyporeflective dots on the cornea, suggesting that they were cystic. AS-OCT confirmed the subepithelial location of lesions. In all patients, the cornea cleared, and visual acuity recovered fully with a short course of topical steroids and lubricants. Conclusions: Mirvetuximab soravtansine therapy can cause transient corneal toxicity. A short course of topical steroids can reduce the patient symptoms.